Prevalence and causes of vision loss in sub-Saharan Africa in 2015: magnitude, temporal trends and projections - Naidoo, Kovin Shunmugam; Kempen, John H.; Gichuhi, Stephen; Braithwaite, Tasanee; Casson, Robert J.; Cicinelli, Maria Vittoria; Das, Aditi; Flaxman, Seth R.; Jonas, Jost B.; Keeffe, Jill Elizabeth; Leasher, Janet; Limburg, Hans; et al. (British journal of ophthalmology, 2020)
Background This study aimed to assess the prevalence and causes of vision loss in sub-Saharan Africa (SSA) in 2015, compared with prior years, and to estimate expected values for 2020. - Methods A systematic review and meta-analysis assessed the prevalence of blindness (presenting distance visual acuity <3/60 in the better eye), moderate and severe vision impairment (MSVI; presenting distance visual acuity <6/18 but ≥3/60) and mild vision impairment (MVI; presenting distance visual acuity <6/12 and ≥6/18), and also near vision impairment (<N6 or N8 in the presence of ≥6/12 best-corrected distance visual acuity) in SSA for 1990, 2010, 2015 and 2020.In SSA, age-standardised prevalence of blindness, MSVI and MVI in 2015 were 1.03% (80% uncertainty interval (UI) 0.39-1.81), 3.64% (80% UI 1.71-5.94) and 2.94% (80% UI 1.05-5.34), respectively, for male and 1.08% (80% UI 0.40-1.93), 3.84% (80% UI 1.72-6.37) and 3.06% (80% UI 1.07-5.61) for females, constituting a significant decrease since 2010 for both genders. There were an estimated 4.28 million blind individuals and 17.36 million individuals with MSVI; 101.08 million individuals were estimated to have near vision loss due to presbyopia. Cataract was the most common cause of blindness (40.1%), whereas undercorrected refractive error (URE) (48.5%) was the most common cause of MSVI. Sub-Saharan West Africa had the highest proportion of blindness compared with the other SSA subregions. - Conclusions Cataract and URE, two of the major causes of blindness and vision impairment, are reversible with treatment and thus promising targets to alleviate vision impairment in SSA.
Gesehen am 15.02.2021